Leadership practices in two successful primary schools in Soweto, South Africa educating learners afflicted by multiple deprivation - Hoosier, Brianetta (My University, 2019)
The study investigated the ways in which principals and other school leaders navigated issues of multiple deprivation to achieve high academic performance. The study was grounded in the theoretical framework of the University of Chicago Consortium on Chicago School Research (Bryk, Sebring, Allensworth, Easton, & Luppescu, 2010), which proposes five essential supports (5 Essentials) for successful schools. The framework was the lens used to understand whether or not successful school leaders implemented these five essentials supports in response to their learners’ battle with multiple deprivation. The main research question of the study is: what can we learn about school improvement from the leadership practices of successful school leaders in primary schools educating learners afflicted by multiple deprivation in Soweto? Interviews were conducted with two principals, three School Management Team (SMT) members, and three educators. Using thematic content analysis, recurrent themes emerged including stakeholders involvement, policy, academic support, progress monitoring, collaborative teachers, teacher quality, team building, parental involvement, and distributed leadership. In the South African context, this study expands the 5 Essentials framework through a contribution toward the emergence of a model of leadership practices of successful school leaders educating learners afflicted by multiple deprivation in primary township schools. In this model, the four core leadership practice with related themes, explain the leadership practices that underpin learner achievement. The core leadership practices and themes includes: (1) safety practices: stakeholder involvement and policy; (2) instructional practices: collaborative teachers; 3 (3) teacher quality and team building academic practices: academic support and progress monitoring; and (4) family engagement practices: parental Involvement (Biological or Proxy)
A thesis submitted to the Wits School of Education, Faculty of Humanities, in accordance with the requirements for the degree of Doctor of Philosophy at the University of the Witwatersrand. January 2019
Keywords: Educational leadership; School management and organization--South Africa; System analysis